Meir Sternberg, Raccontare nel tempo (II): Cronologia, Teleologia, Narratività (ENTHYMEMA, 2009)
We present the Italian translation of the first part of "Telling in Time II: Chronology, Theleology, Narrativity", by M. Sternberg (the second part will be published in Enthymema, 1 2010).